Abstracts of the 17th European Conference on Eye Movements 2013 - Kenneth Holmqvist; Fiona Mulvey; Roger Johannson (Bern Open Publishing, 2013)
This document contains all abstracts of the 17th European Conference on Eye Movements, August 11-16 2013 in Lund, Sweden ECEM 2013 has been the 17th European Conference on Eye Movements, with the original aims 'to exchange information on current research, equipment and software' remaining at the forefront. ECEM is transdisciplinary, promoting new approaches, co-operation between research fields and communication between researchers. It has grown from it's origins as a small, specialist conference to a large international event, covering all aspects of basic and applied research using eye movements ( see information from previous conferences in the archive). Today, ECEM is the largest conference on eye movements in the world, based on number of submissions. In keeping with the tradition of supporting young researchers and promoting new research. In the days prior to the conference, ECEM 2013 has included methods courses for all interested delegates on several aspects of eye movements research and applications, led by top international experts (see method workshops). Panel discussions during the conference have provided a forum for communication between researchers, manufacturers and interface designers on new and emerging themes in eye movements research and technology.(see program). The exhibition included top eye tracker manufacturers (see exhibition). ECEM 2013 bought together neurophysiologists, psychologists, neuropsychologists, clinicians, linguists, computational and applied scientists, engineers and manufacturers interested in the movements of the eyes, with an emphasis on learning from each other and promoting development of the field. This ECEM was hosted by the Eye Tracking Group at Lund University, Sweden, and organised by the Eye Movement Researcher's Association (EMRA) and the COGAIN (communication through gaze interaction) association, to promote interdisciplinary, basic and applied research excellence.